PENGARUH KOMUNIKASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BOYOLALI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Rahayu Triastity, El Arwinto Luwarno, Amin Wahyudi & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The influence of Communication and leadership against theperformance of the employees of the Secretariat of this research aims toanalyze the influence of communication and leadership against theperformance of an employee with discipline as intervening variable. Thisstudy used a survey method, the type of data the data used was qualitativeand quantitative data, the source data used the primary data and secondarydata. The population in this study are all employees of the Secretariat of theHouse of representatives District of Boyolali 52 employees. The number ofsamples in the study as many as 52 employees, so it is a research census.Methods of data collection were used: questionnaire. Technique of dataanalysis used the test of validity, reliability test, test the assumptions ofclassical, and path analysis. The results of the analysis of the data obtainedto the conclusion that: the communication and leadership of the influentialsignificantly to discipline employees work the Secretariat RepresentativesBoyolali Regency Area. Communication, leadership and discipline work effectsignificantly to the performance of an employee of the Secretariat of theRegional House of representatives Boyolali Regency. Discipline workmediated influence of communication and leadership against theperformance of the employees of the Secretariat of the Regional House ofrepresentatives Boyolali Regency.Keywords: communication, leadership, work discipline, performance